The Effect of Digitalization and Customer Relationship Management on Member Loyalty - Erlangga, Azies Wahyu (Inkubis : Jurnal Ekonomi dan Bisnis, 2023)
The study aims to find out and describe the influence of digitalization variables, and customer relationship management on member loyalty at BMT NU Artha Berkah, Cirebon Regency in the Millennial Generation. This research uses quantitative research methods. With a population of 185 active members who use products and services at BMT NU Artha Berkah, Cirebon Regency, then the sample was calculated using the slovin technique and was obtained at 126. The results of this study show that partially there is no significant influence between digitalization variables on member loyalty variables and a significance value of 0.842 which is > 0.05. Then there is influence and significant relationship between the customer relationship management variable and the member loyalty variable with a significance value of 0.000 which is <0.05. And simultaneously the digitization variable and the customer relationship management variable affect the member loyalty variable with a significance value of 0.000 which is <0.05.